MORPHOLOGICAL-SYNTACTIC STRUCTURE AND SEMANTIC CHARACTERISTICS OF EUPHEMISTIC TWO-BASE COMPOUND WORDS IN GERMAN - Nurqulov Javlon Rashid o’g’li (International Journal of Literature and Language Studies, 2026)
This article examines the morphological and syntactic structure of euphemisms belonging to the category of two-base noun compounds, alongside a comprehensive analysis of their semantic characteristics.